The roles of ameliorants on tree seedling growth for land rehabilitation - Slamet Budi Yuwono; Alawiyah Alawiyah; Melya Riniarti; Dermiyati Dermiyati (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Yuwono SB, Alawiyah, Riniarti M, Dermiyati. 2021. The roles of ameliorants on tree seedling growth for land rehabilitation. Biodiversitas 22: 2706-2714. Revegetation of the limestone post-mining land using trees with ameliorants is expected to improve land quality and soil biodiversity. This research aimed to accelerate the seedling growth of tree species namely sengon (Paraserianthes falcataria), agarwood or gaharu (Aquilaria malaccensis), and acacia (Acacia mangium) on limestone post-mining soil media by applying various types of ameliorants. The experimental design was a Completely Randomized Design consisting of 7 treatments with three replications, namely P0 (without ameliorant or control), P1 (humic acid [HA], 4 kg ha-1), P2 (phosphate rocks [PR], 350 kg ha-1), P3 (arbuscular mycorrhizal fungi [AMF], 500 spores plant-1), P4 (HA+AMF), P5 (PR+ AMF), and P6 (HA+PR+AMF). The variance analysis of data were done at the significance level of 0.05 and continued with the LSD test. The combination of ameliorants HA and AMF gave the highest root nodules number in 3-month-old P. falcataria with the percentage of effective nodules in absorbing N of 100% at 12 weeks after planting. Ameliorant application did not affect the root nodule number, the percentage of effective nodules, and the percentage of root infection by mycorrhizae in 3-month-old A. mangium. The combination of ameliorants PR and AMF gave the highest percentage of root infection by mycorrhizae in 4-month-old A. malaccensis. The tree dependence level on mycorrhizae was categorized as highly dependent on A. malaccensis, marginally dependent on P. falcataria, and independent on A. mangium.